Prediksi Jumlah Pendapatan Bisnis Katring Rumahan Menggunakan Metode Fuzzy Tsukamoto - Parlina, Iin; Sari, Ika Purnama; Irawan, Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Home catering business is a growing business with a system that depends on the number of orders and production costs that are not fixed in each period [1]. This condition makes it difficult for business owners to predict income accurately. Based on this, this study aims to build a revenue prediction system using the Fuzzy Tsukamoto Method that is able to process data on the number of orders and production costs as variables as objects to measure the value of income in a home catering business. The data source for this study was collected based on order production data. The data used in this study is questionnaire data with a simple random sampling technique. The sample of respondents was 50 respondents. The variable used was the number of catering orders produced based on the income value. The method used to solve this case is to utilize data mining techniques with the Fuzzy Tsukamoto method. The data was processed using visual studio software and calculated from 3 variables, namely the order variable (P1) has a Fuzzy set with few and many, the price variable (H) has an affordable and low set, and the income variable (P2) has a low and high set. The predicted revenue of the catering business resulted in orders for 750 boxes at a price of Rp. 25,000, with a predicted weekly revenue of Rp. 25,750,000. This can be used as input for home catering businesses.